'I am Italian in the world': a mobile student's story of language learning and ideological becoming. (2nd July 2016) - Harvey, Lou
ABSTRACT: This article theorises the relationship between language and intercultural learning from a Bakhtinian dialogic perspective, based on the language learning story of Federica, a mobile student in UK higher education (HE). I first outline the context of UK HE and its internationalisation agenda, discussing how research in this field has conceptualised language, intercultural communication (IC) and international students in terms of a totalising boundary between self and other . I link this to current concerns in IC regarding the philosophical underpinnings of the field, specifically the aporia created as a result of the totalising self/other relation in prevailing IC discourse. I then present a means of addressing this aporia through a Bakhtinian theorisation of the relationship between language and intercultural learning. This theorisation offers a relational perspective on the self and the other in which intercultural learning is a process of ideological becoming with the other, enacted in, with and through language, as illustrated in Federica's story of learning English. The article concludes with a call for language and communicative practices to be placed at the heart of HE internationalisation agendas and for HE practitioners to recognise shared responsibility for IC.